Harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification: fixed metallized polypropylene film dielectric a.c. and pulse capacitors. Assessment level E. (30th November 1990) - British Standards Institution,
No abstract available